Vous êtes sur la page 1sur 14

Damped Harmonic Motion

Prerequisites
You should already be familiar with the solution to homogeneous, constant coefficient second
order differential equations, with simple harmonic motion and with sinusoidal functions.

Damped vibrations and linear
linear resistive forces
Damped vibrations occur when the amplitude of an oscillating system progressively decreases.

displacement

time

To study damped vibrations we must begin by reviewing undamped vibrations. Undamped
oscillations occurs when an object oscillates under simple harmonic motion.

Simple harmonic motion
Simple harmonic motion is defined as motion taking place along a straight-line in which the
 d 2x 
acceleration  2  of the object is proportional to the displacement (x ) of the object from a
 dt 
fixed point and in the opposite direction to the displacement. The differential equation governing
d 2x
simple harmonic motion is = −ω 2x with solution x = A sin ωt or x = A cos ωt or a linear
dt 2
combination of both depending on the initial conditions.

Copyright Black’s Academy Limited February 2008

1

b and c are positive constants. It is these linear resistive forces that lead to the damping of the oscillation. x (t ) A y = Asin (ωt) t/s 0 2π ω –A Damped oscillations occur when an equation takes the form d 2x dx a +b + cx = 0 dt 2 dt where a. the liquid progressively slows down the mass. However. It is displaced from its equilibrium position and starts to oscillate. Comparing this to the case for undamped simple d 2x dx harmonic motion + ω 2x = 0 we see that a term for the velocity of the particle. . Expressions like arise in situations where a particle is subject to dt linear resistive forces. spring liquid mass Copyright Black’s Academy Limited February 2008 2 . the oscillations remain constant. the mass undergoes damped oscillation. has dt 2 dt dx appeared in the equation. suppose an object is suspended by a spring and is immersed in a bucket of a viscous liquid. Consequently. so the amplitude of the oscillations progressively decreases. A linear resistive force is a force acting on a particle whose magnitude is proportional to the speed at which the object is moving and whose direction opposes the velocity of the object. For example. Hence.The graph of x = A sin ωt is a simple sine wave with constant amplitude.

It is then subject to three forces. let Young’s modulus be λ . l0 T d W The mass is subject to two forces.) We shall now show how a system of this kind can lead to a differential equation of the form d 2x dx a +b + cx = 0 dt 2 dt Let the mass of the particle be m. The resistive force is understood to oppose the motion dt of the particle. We will suppose the spring is displaced by x = x (t ) from its equilibrium position.The motion of a mass oscillating in air will also be opposed by air resistance and so will undergo damped oscillations. When the mass hangs under its own weight in the equilibrium position the forces may be drawn as follows. by considering what happens at the equilibrium position first. The mass is given by W = mg . Since the system is in equilibrium T =W λ d = mg l0 Now suppose that the mass is displaced from the equilibrium position by a further x = x (t ) . the tension in the spring pulling it upwards and the weight λ pulling it downwards. we start to study such systems. The tension (T ) due to the extension of the spring. as usual. (The point of the liquid in this example is to make the effect of damping more obvious. The tension is given by d where d is the extension of the spring up to l0 the equilibrium point. However. its weight Copyright Black’s Academy Limited February 2008 3 . let the natural length of the spring dx be l0 and let the magnitude of the resistive force of the treacle be R = r where r is a constant dt dx and v (t ) = is the velocity of the mass.

l0 T F d+x W R In the diagram above we imagine that the mass is about to move upwards.  dx  (W = mg ) and the linear resistive force  R = r arising from the opposition to motion of the  dt  fluid or air. as usual W = mg The linear resistive force is dx R = −r dt It acts as to oppose the motion. we show it pointing downwards. The resultant force acting on the particle is F =T + R +W and by Newton’s second law this is d 2x F = ma = m dt 2 Hence d 2x λ dx m = − (d + x ) − r + mg dt 2 l0 dt λ λ dx =− d − x −r + mg l0 l0 dt Copyright Black’s Academy Limited February 2008 4 . which is shown by the negative sign. The weight is. As the linear resistive  dx  force  R = r opposes the motion. The total extension is  dt  d + x and the tension is λ T =− (d + x ) l0 The negative sign indicates that the tension is in the opposite direction to the displacement.

If ∆ = 0 then m1 = m2 and the root is real and repeated. The dashpot is represented thus dx Its function is to provide a linear resistive force R = −r where r is the dashpot constant. λ Since d = mg we have l0 d 2x dx λ m 2 = −r − x dt dt l0 d 2x dx λ m 2 +r + x =0 dt dt l 0 which is a second order homogeneous constant coefficient differential equation. The dt whole car suspension system can be represented by the following. In order to bring about the damping the suspension system is fitted with a mechanical device called a dashpot. We will be initially considering the case where the tyre runs over a single bump. If ∆ < 0 the roots m1 and m2 are conjugate complex numbers where m1 = α + i β and m2 = α − i β . If ∆>0 the roots m1 and m2 are real and distinct. Copyright Black’s Academy Limited February 2008 5 . the auxiliary equation is dt 2 dt a m2 + b m + c = 0 with roots m1 and m2 and discriminant ∆ = b 2 − 4ac . which effectively gives it a sudden sharp displacement from its equilibrium position. b and c are constants. the solution to the original differential equation takes the form x (t ) = ( A + Bt ) em1t where A and B are constants. the solution to the original differential equation takes the form x (t ) = eαt ( A sin β t + B cos β t ) where A and B are constants. Dashpots The purpose of a car suspension system is to bring about the damping of oscillations in a tyre as it runs over a bump. the solution to the original differential equation takes the form x (t ) = Aem1t + Bem2t where A and B are constants. Second order homogeneous constant coefficient differential equations d 2x dx Given a +b + cx = 0 where a.

Find its equation of motion and its phase lag. Solution The system can be represented as follows. Find its maximum amplitude subsequent to the displacement. this force may also be represented by dashpot symbol. dashpot and spring have no mass. CHASIS k. frequency and period. so we will continue to deal with the solution to questions where the oscillating mass is given by the object here labelled the tyre. In other mechanical systems where there is a linear resistive force. This creates complications in the mathematics that we wish to avoid at this stage. and the object labelled by the chassis is fixed.5 m. Example (1) A mass. m of 2 kg. its angular frequency. and we are imagining that the tyre. Copyright Black’s Academy Limited February 2008 6 . The symmetry of the situation means that what applies to a tyre of mass m where the chassis is fixed and has no mass would also apply to a chassis of mass m where the tyre is fixed and has no mass. Sketch a graph showing the subsequent motion. It is subject to a sudden sharp displacement of 0. l 0 SPRING DASHPOT r TYRE In this application the oscillating mass is provided by the chassis. is suspended by a spring of natural length l0 = 2m and Young’s modulus λ = 10 N and by a dashpot with dashpot constant r = 2 .

l 0 r Let x = x (t ) represent its displacement at time t after it receives the shock.5t ) + B cos (1.5t ( A sin (1. t = 0 Copyright Black’s Academy Limited February 2008 7 .5B sin (1. The auxiliary equation is 2n 2 + 2n + 5 = 0 −5 ± 25 − 34 n= 2 −1 ± −9 = 2 −1 ± 3i = 2 = −0.5t ( A sin (1.5i The solution is complex which indicates that there are oscillations.5t ) ) We need to determine the constants A and B. Then x ( 0 ) = 0.5 implies B = 0. r = 2.5 .5t ) ) + e −0. The general solution is x (t ) = e −0. k. so x ( 0 ) = 0.5 . λ = 10. The general equation of motion for this system is d 2x dx λ m 2 +r + x =0 dt dt l 0 Here m = 2. l0 = 2 . dt Differentiating x (t ) gives dx v (t ) = = −0.5 ± 1.5 and dx also v ( 0 ) = ( 0 ) = 0 since it is not moving at t = 0 .5t (1.5t ) ) dt Substituting v ( 0 ) = 0. We have initial conditions x ( 0 ) = 0.5A cos (1.5t ) + B cos (1. Hence d 2x dx 2 +2 + 5x = 0 dt 2 dt We now proceed to solve this equation.5t ) − 1.5e −0.

5 6 Therefore.5t ) + cos (1.5t ) + cos (1. = 0.527 (3 s.5B + 1.) So the phase lag of 0.5 0 = −0. The frequency is Copyright Black’s Academy Limited February 2008 8 .5t ) cos φ − sin (1.322) ) The phase lag is given by 1.f.. Let 1 1 sin (1.5t ( 0.5t ) = R cos (1. The angular velocity of the damped oscillation is ω = 1.52704.215 s (3 s.5t − 0.5t ) = R ( cos (1..5A 0.322 rad −1 (3 s. the equation of motion is 1 1  x (t ) = e −0.5t ) sin φ ) 6 2 1 1 R cos φ = R sin φ = − 2 6 R cosφ = 0. = 0 t = 0.5t  sin (1.25 1 A= = 1..527 cos (1.32175.0 = −0.5 φ = –0.f..215 s.5 rad s−1 ..)  6   2 So the equation of motion can also be written x (t ) = e −0..5t + φ ) 6 2 where φ is the phase lag. Then 1 1 sin (1.322 rad 1 R sinφ = – R 6  1  −   1 6 φ = tan     = − . = −0.5t ) + cos (1.5t )  6 2  The presence of both a sine and cosine element in the part determining the oscillations indicates that there is a phase lag.25 + 1.5A Since B = 0.f.)   1  3   2      2 2  1 1 R =   +   = 0.322 rad corresponds to a time of 0.5t − 0.

527 cos (1.f.5t ( 0.527 cos (1.5 m due to the initial displacement. at which point the displacement will be  π  −0.527 cos (1.322) –0.5 f = = = 0.322 rad° –0.5t .5t − 0.0.5t − 0.5 Regarding this sketch note that because of the damping factor the maxima of x (t ) = e −0.527cos (1.5 In every half cycle the velocity is zero and the amplitude is at a maximum.5t .322) ) is as follows. Copyright Black’s Academy Limited February 2008 9 .0.215 s before the maxima of the corresponding undamped function x (t ) = 0.5 x (t) = 0.5t − 0.19 s (3 s.527 cos (1.5t x (t) = e –0.5t is not in fact tangent to x (t ) = e −0.5t ( 0.)   A sketch of the graph of x (t ) = e −0. The graph of the damping function x (t ) = e −0.322) ) .f.527 cos (1.215 s ≡ 0.239 Hz (3 s.5t ( 0.) 2π 2π The period is 2π 2π T = = = 4. At = s the velocity will again be 2 1.) ω 1.5t x (t) = –e 2π Period = 1.322) ) occur φ = 0. ω 1.322 rad ≡ 0.5  1 1  x (t ) = e  1.322) . x 0.322) t Phase shift = 0.5   6 sin ( 0 ) + 2 cos ( −π )  = −0.f.5 zero. At t = 0 the T π amplitude is 0.5t − 0.5t x (t) = e 0.175 m (3 s.

the solution takes the form x (t ) = ( A + Bt ) e µ1 . Copyright Black’s Academy Limited February 2008 10 . x –µ 1 t x (t) = (A + Bt )e t 0 The case of critical damping (2) µ1 . The system does not oscillate but experiences an immediate exponential decrement returning it to the equilibrium position. lo = natural length The theory of homogenous second order constant coefficient differential equations tells us that this has solutions depending on the nature of the roots to the auxiliary equation λ mx 2 + rx + =0 l0 Suppose µ1 . there are three cases: (1) If µ1 = µ2 is a real repeated root.Critical and non- non-critical damping We have seen that the general equation of motion for a system subject to linear resistive force and consequently subject to damping is d 2x dx λ m +r + x =0 dt 2 dt l0 m = mass. This is called critical damping. λ = Young's moduls. The system does not travel beyond the equilibrium position. and is brought back to the equilibrium position. r = constant of linear resistance. µ2 are the two roots of this equation. Then. The motion is not oscillatory. This indicates a situation where there is overdamping. µ2 are real and distinct ( µ1 ≠ µ2 ) then x (t ) = Ae µ t + Be µ t 1 2 In the case where there is a linear resistive force the roots µ1 and µ2 will both be negative.

Hence. generally we expect a phase lag. Copyright Black’s Academy Limited February 2008 11 . the system oscillates but the amplitude of the oscillations is damped. µ2 are complex conjugate numbers so that µ1 = α + i β µ2 = α − i β then the solution is x (t ) = eαt ( A sin β t + B cos β t ) Again the requirement that the linear resistive force acts in the opposite direction to the velocity entails that α is a negative quantity. x –αt x (t) = e t Phase shift –αt x (t) = –e The case of underdamping As the graph indicates. x –µ 1t –µ 2t x (t) = Ae + Be Overdamping Critical damping t 0 The case of overdamping (3) If µ1 .

therefore. r = constant of linear resistance. It returns the system to the equilibrium position at the fastest possible rate without overshooting the equilibrium position. α <1 When α = 1 we have the case of the single repeated root r λ=− 2m with solution x (t ) = ( A + Bt ) e λt . When such things as gun recoil mechanisms are designed. Examining the equation d 2x dx m +r + kx = 0 m = mass. it is this that is selected. where α = 1 . This situation. x α>1 α=1 t α<1 Copyright Black’s Academy Limited February 2008 12 . k = spring constant dt 2 dt with the auxiliary equation mx 2 + rx + k = 0 We require that the discriminant ∆ = r 2 − 4mk < 0 4mk > r 2 r2 <1 4mk Let us define r2 r α= = 4mk 2 mk to be the damping factor.The criterion for critical damping For oscillations to take place there must be complex roots. is called critical damping. The requirement for oscillations to take place is.

then at A1 = Aeαt1 where t1 is the first value such that bt + φ = 0 Then the second peak occurs at t = t1 + T and the nth at t = t1 + nT . x –αt x (t) = e A1 A2 t A1′ A 2′ –αt x (t) = –e The diagram marks the successive amplitudes of the oscillations. Successive peaks occur when β cos (bt + φ ) = 1 i. after intervals of the period T. Let A1 represent the first peak.Amplitude of successive oscillations Consider the case where the damping factor α < 1 so there are damped oscillations.2 = 2m and −r r 2 − 4mk α= and β = 2m 2m 2π The angular frequency is given by β so the period is T = . The general solution is x (t ) = eat ( A cos ( β t + φ ) ) where λ1 = α + i β and λ2 = α − i β are the two complex conjugate solutions to the equation mx 2 + rx + k = 0 Hence −r ± r 2 − 4mk λ1. Hence Copyright Black’s Academy Limited February 2008 13 . This occurs after every complete oscillation – that is.e. when bt + φ = 0 .

That is. Copyright Black’s Academy Limited February 2008 14 . the amplitude of successive oscillations decreases with time in geometric progression with common ratio e −T . α (t1 + (n −1)T ) An +1 = Ae ( 1 ) α t +nT An = Ae and Hence the ratio α (t + (n −1)T ) An Ae 1 = α (t +nT ) An +1 Ae 1 α (t1 + (n −1)T ) −α (t1 +nT ) =e = e −T So successive peaks maintain a constant ratio.